2012
DOI: 10.1109/jstsp.2012.2194474
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Geometry and Color Information for Scene Segmentation

Abstract: Scene segmentation is a well-known problem in computer vision traditionally tackled by exploiting only the color information from a single scene view. Recent hardware and software developments allow to estimate in real-time scene geometry and open the way for new scene segmentation approaches based on the fusion of both color and depth data. This paper follows this rationale and proposes a novel segmentation scheme where multidimensional vectors are used to jointly represent color and depth data and normalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 21 publications
0
69
0
1
Order By: Relevance
“…In order to obtain robust non-local cost aggregation, those regions should be merged together. Using both color and disparity cues is also proved to be helpful for improving scene segmentation [58,59].…”
Section: Methods Based On Aggregation Over Segment-treementioning
confidence: 99%
“…In order to obtain robust non-local cost aggregation, those regions should be merged together. Using both color and disparity cues is also proved to be helpful for improving scene segmentation [58,59].…”
Section: Methods Based On Aggregation Over Segment-treementioning
confidence: 99%
“…Our observation is that neighboring regions with different color distributions might still have similar disparities, and such regions should be merged for robust cost aggregation. Besides, it has been shown that improved scene segmentation results can be achieved when both cues are exploited as feature vectors [9,12].…”
Section: Enhancement With Color-depth Segmentationmentioning
confidence: 99%
“…Such ambiguity and uncertainty in representation should be considered, in data modelling for sake of robustness/ efficiency. Probability theory was the first model used to cope with value uncertainty problem, but they are not suitable to solve ambiguity categorizing problem [13]. Theories based on Fuzzy sets [14], proposed later on, by Zadeh, can model ambiguity but they fail in case of uncertain data.…”
Section: Introductionmentioning
confidence: 99%